2022
DOI: 10.1186/s12915-022-01379-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the picocyanobacteria salinity divide through ecogenomics of new freshwater isolates

Abstract: Background Cyanobacteria are the major prokaryotic primary producers occupying a range of aquatic habitats worldwide that differ in levels of salinity, making them a group of interest to study one of the major unresolved conundrums in aquatic microbiology which is what distinguishes a marine microbe from a freshwater one? We address this question using ecogenomics of a group of picocyanobacteria (cluster 5) that have recently evolved to inhabit geographically disparate salinity niches. Our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 167 publications
10
51
0
Order By: Relevance
“…Rhodanases, (aryl)sulfatases and ABC transporters for sulfate (e.g. CysWT, CysPA) were detected in freshwater members, but not in marine isolates, probably as adaptations to limited sulfur amounts available in freshwater systems (Cabello‐Yeves, Callieri, et al, 2022; Cabello‐Yeves, Scanlan, et al, 2022). As expected, genes involved in the transport and biosynthesis of compatible solutes (betaine biosynthesis/transport–sarcosine N ‐methyltransferase, dimethylglycine N ‐methyltransferase; high‐affinity choline uptake protein BetP) are only present in marine and/or brackish isolates, providing a molecular basis for the salinity divide (Cabello‐Yeves, Callieri, et al, 2022; Cabello‐Yeves, Scanlan, et al, 2022).…”
Section: Prokaryotic Lineages With Known Habitat Transitionsmentioning
confidence: 99%
“…Rhodanases, (aryl)sulfatases and ABC transporters for sulfate (e.g. CysWT, CysPA) were detected in freshwater members, but not in marine isolates, probably as adaptations to limited sulfur amounts available in freshwater systems (Cabello‐Yeves, Callieri, et al, 2022; Cabello‐Yeves, Scanlan, et al, 2022). As expected, genes involved in the transport and biosynthesis of compatible solutes (betaine biosynthesis/transport–sarcosine N ‐methyltransferase, dimethylglycine N ‐methyltransferase; high‐affinity choline uptake protein BetP) are only present in marine and/or brackish isolates, providing a molecular basis for the salinity divide (Cabello‐Yeves, Callieri, et al, 2022; Cabello‐Yeves, Scanlan, et al, 2022).…”
Section: Prokaryotic Lineages With Known Habitat Transitionsmentioning
confidence: 99%
“…Within freshwater ecosystems, isolates from the family Methylophilaceae (class Gammaproteobacteria) show a smaller genome size for pelagic than for sediment dwellers [ 20 ]. Additionally, two studies have shown that marine Cyanobacteria have smaller genome sizes than freshwater [ 21 , 22 ]. This literature already provides some insights on how genome size is linked to the environmental heterogeneity of freshwater and marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 21, 2022. ; https://doi.org/10.1101/2022.10.20.512849 doi: bioRxiv preprint freshwaters (Hugerth et al, 2015), while picocyanobacteria show the opposite trend (Cabello-Yeves et al, 2022). Further research must be done to understand how genome sizes vary between and within different aquatic environments, particularly brackish water bodies including pelagic and benthic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Within freshwater ecosystems, we can observe that isolates from the family Methylophilaceae (class Gammaproteobacteria) show a decrease in genome size in the transition from sediments to pelagic forms (Salcher et al, 2019). Additionally, several studies have shown that marine microbes have smaller genome sizes than freshwater microorganisms (Cabello-Yeves et al, 2022; Chen et al, 2021; Rodríguez-Gijón et al, 2022). Yet, genome size variation in the brackish realm remains debated: Actinobacteria in the brackish Baltic Sea show bigger genome sizes than in freshwaters (Hugerth et al, 2015), while picocyanobacteria show the opposite trend (Cabello-Yeves et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation